Characterization of Phytocomponents of Mindi Leaf Extract and Chinese Petai Seeds by LC-HRMS and In Silico Activity Against Alpha-glucosidase - Maharani, Maharani; Elya, Berna; Forestrania, Roshamur Cahyan (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Melia azedarach L. and Leucaena leucocephala L. were two plant species that had attracted attention in phytochemical research due to their bioactive potential. However, research on the phytochemical characterization using Liquid Chromatography – High-Resolution Mass Spectrometry (LC-HRMS) of these two plants was still limited. This study was to identify and characterize the phytochemical properties of Mindi leaves (Melia azedarach L.) and Chinese Petai seeds (Leucaena leucocephala L.), as well as to conduct an in silico study. The research method involved reflux extraction using 70% ethanol as the solvent, qualitative phytochemical identification, and characterization using LC-HRMS. The compounds from LC-HRMS from each extract were analyzed for their bioactivity in silico. The results showed that Mindi leaves (M. azedarach L.) and  Petai cina seeds (L. leucochepala L.) contain alkaloids, saponins, phenolics, flavonoids, and tannins. The results of LC-HRMS analysis showed that 10 compounds were identified in each extract, and 3 of them were Prolylleucine, (3beta, 24R, 24'R)-fucosterol epoxide, and 2,3-Dihydro-1-benzofuran-2-carboxylic acid that is a compound found in both extracts. In silico results show that there is 1 compound in mindi leaf extract, namely Methyl isonicotinic, and 3 compounds from petai cina seed extract, namely trans-p-Coumaraldehyde, L-alanine, and 3-Buten-1-amine, which show pretty strong alpha-glucosidase inhibitory activity inhibits the target protein 3A4A. This research can be a reference for developing mini leaf extract and petai cina seeds as anti-diabetic candidates.